Art in the Global Present - Papastergiadis, Nikos; Lynn, Victoria (UTS ePRESS, 2014)
Art in the Global Present presents a fascinating collection of essays that together reveal how art is currently navigating a globalised world. It addresses social issues such as the impact of migration, the 'war on terror' and the global financial crisis, and questions the transformations produced by new forms of flexible labour and the digital revolution. Through examining the resistance to the politics of globalisation in contemporary art, presenting the construction of an alternative geography of the imagination and reflecting on art's capacity to express the widest possible sense of being, this book explores the worlds that artists make when they make art. A multifaceted perspective on the complexity of these issues is reached through the words of a diverse range of art practitioners and commentators, including acclaimed artists Lucy Orta, Callum Morton, Danae Stratou and the collective Postcommodity, international curators Hou Hanru, Cuauhtémoc Medina, Ranjit Hoskote and Linda Marie Walker and art critics, academics, writers and theorists Jean Burgess, Paul Carter, Barbara Creed, Geert Lovink, Scott McQuire, Nikos Papastergiadis, Gerald Raunig and Jan Verwoert.